Influence of Transverse Shearing and Rotary Inertia on Vibrations of a Fibrous Composite Beams - GOŁAŚ, J. (Engineering Transactions, 2007)
The aim of the paper was determination of the influence of transverse shear deformation and rotary inertia on the natural frequencies and on the values of displacements of beams made of fibrous composites reinforced with layers of long fibres. It was assumed that the matrix of the composite beam possesses linear elastic and transversally isotropic properties. Moreover, a reinforcement in the form of layers composed of long fibres symmetrically located in the crosssection was considered. In order to describe the displacement and strain state of the matrix, the Timoshenko theory was applied. Using the complete analytical solutions obtained in the paper, the accuracy analysis of the results was performed and compared with the theory of Bernoulli beams.